2010
DOI: 10.1515/sg-2010-0018
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters for Bud Flushing and Growth Characteristics of White Spruce Seedlings

Abstract: We estimated heritabilities and correlations for bud flushing and growth traits of white spruce seedlings, and the correlations of seedling traits with 10-and 11-year height of the same families in the field. The seedling greenhouse experiment had a randomized complete block design with 30 replications, 58 open-pollinated families and single-tree plots. Individual tree heritability (h i 2 ) was 0.78 and 0.54 for 18 (H18) and 36 (H36)-week total height, respectively. The corresponding heritabilities for family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(19 reference statements)
0
6
0
1
Order By: Relevance
“…In order to establish both species breeding strategies and the rules for transfer of forest reproductive material, the correlations between bud flushing and growth traits should be known. To safeguard trees against late spring frost and early fall frost, superior growth potential should be independent of shoot phenology and duration of the growing season (Rweyongeza et al 2010). Overall, we found significant correlations between phenology and growth in both experiments but in different directions.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In order to establish both species breeding strategies and the rules for transfer of forest reproductive material, the correlations between bud flushing and growth traits should be known. To safeguard trees against late spring frost and early fall frost, superior growth potential should be independent of shoot phenology and duration of the growing season (Rweyongeza et al 2010). Overall, we found significant correlations between phenology and growth in both experiments but in different directions.…”
Section: Discussionmentioning
confidence: 64%
“…Variation in the timing of bud flushing has implications in the susceptibility of genotypes to frost damage and may determine a variation of annual height growth , Rweyongeza et al 2010. Moreover, information on the genetic variation and inheritance of adaptive traits is extremely important in species breeding programme, both for the delineation of provenance regions and the production of high-quality timber.…”
Section: Introductionmentioning
confidence: 99%
“…Granhus et al (2019) also reported a relationship between shoot formation and the latitude of the origins in Picea abies, with the frequencies of trees with multiple shoots decreasing with increasing elevation. Similarly, Rweyongeza et al (2010) observed negative association between height and latitude, longitude, and elevation of seed sources in Picea glauca in a seedling study. Significant provenance effects on growth and the number of flushes were observed in Pinus taeda, with the southern populations having more growth and more frequent flushing (Quesada et al 2017).…”
Section: Seed Source Variationmentioning
confidence: 76%
“…Mrazuvzdornosť a fenologické znaky vykazujú nízke až stredné hodnoty dedivosti v užšom zmysle (Bower & Aitken 2006;O'Neill et al 2000;Rweyongeza et al 2010), čo je dokladom existencie aditívnej genetickej variability a teda aj evolučného potenciálu. V provenienčných pokusoch ako základnom type presadzovacích pokusov (common-garden experiments) u lesných drevín fenologické znaky často vykazujú klinálnu premenlivosť pozdĺž geografických či ekologických gradientov (Daehlen et al 1995;von Wuehlisch et al 1995;Wright 1976).…”
Section: Genetické Aspekty Odozvy Na Vplyv Klímyunclassified